Frequency of complications in immediate post-partum intrauterine contraceptive device insertion - Benish, Benish; Naz, Tabassum; Waheeda, Waheeda; Khushboo, Khushboo; Parveen, Tooba; Asma, Asma (Journal of Neonatal Surgery, 2025)
Objective: To Determine The Frequency Of Complications (Pid, Expulsion Of Iud) And Missed String) Following Post-Partum Intrauterine Device Insertion Study Design: Descriptive Study. Setting: This Study Was Conducted At Department Of Obstetrics & Gynaecology, Shaikh Zaid Women Hospital, Larakana, Pakistan. Duration: Six Months After The Approval Of Synopsis From December 9, 2019 To June 8, 2020. Materials And Methods: All Patients Who Fulfilled The Inclusion Criteria And Visited To Shaikh Zyed Women Hospital, Larkana Were Included In The Study. Informed Consent Was Taken After Explaining The Procedure, Risks And Benefits Of The Study. Women Underwent Cesarean Delivery; The Iud Inserter Was Inserted Through The Hysterotomy Site After Delivery Of Baby And Placenta. In Those Patients Underwent Vaginal Delivery, It Was Placed In Uterine Fundus With The Help Of Long And Curved Forceps Without Lock (Kelly's Placental Forceps) For Vaginal Insertions. All Patients Were Assessed At 6 Weeks Duration For Complications (Pid, Expulsion Of Iud And Missed String). All The Collected Data Were Entered Into The Proforma Attached At The End And Used Electronically For Research Purpose. Results: Mean ± Sd Of Age Was 28.5±6.6 Years. In Distribution For Mode Of Delivery, 85 (34.6%) Patients Had Vaginal Delivery While 161 (65.4%) Had Cesarean Section. Expulsion Of Iud Was Noted As Most Common Complication I.E. 55 (22.3%) Followed By Missed String 33 (13.4%) And Pelvic Inflammatory Disease (Pid) Was Documented In 16 (6.5%), While 142 (57.8%) Patients Had No Complications. Conclusion: It Is To Be Concluded That Complication Rate Of Post-Partum Intrauterine Device Insertion Is Found To Be Fairly High. It Can Be Avoided If Proper Preventive Measures Are Taken And Increase Awareness Regarding Ppiud And Its Associated Complications ..